Nonlinear Analysis of Compressed Concrete Elements Reinforced with FRP Bars - Wydra, Małgorzata (Materials (Basel), 2020)
Although fiber reinforced polymer (FRP) bars have proved their usefulness in the case of reinforced concrete flexural elements, there are still limited data on their performance in such structures under compression. Despite multiple benefits of using FRP bars as the reinforcement in concrete elements, their potential application as main reinforcement in compressed elements is still very controversial, mainly due to the limited amount of published research results. The presented work partly fulfills this knowledge gap. Two series of theoretical analyses—one based on the stress distribution in the cross-section and the second using the finite elements method (FEM)—with reference to the experimental results are presented. The analyses concern basalt FRP, glass FRP, and steel-reinforced concrete elements under axial compression. There are derived calculations of load–displacement relations and stress values in bars. Damage progression was analyzed as well. Main findings are as follows: (1) a good agreement between calculated failure loads and experimental results has been achieved; (2) potential negative influence of FRP reinforcement on the compressive capacity of the reinforced element should not be neglected; (3) nonlinear FEM analysis is useful in predicting the maximum value of load and damage zones; (4) stress values of only about 100 MPa (much lower than their compressive strength value) were obtained in non-metallic bars. The results might be useful for the further establishment of design rules.